Estudo cefalométrico comparativo dos traçados predictivos e resultados ortodôntico-cirúrgicos em pacientes com face longa - Gimenez, Carla Maria Melleiro; Bertoz, André Pinheiro De Magalhães; Gabrielli, Marisa Aparecida Cabrini [UNESP]; Pereira Filho, Valfrido Antonio [UNESP]; Bertoz, Francisco Antonio [UNESP] (My University, 2012)
The purpose of this research was to compare, by cephalometric analysis (McNamara and Legan & Burstone) the predictive tracings (by methods manual, and by softwares Dentofacial Planner Plus and Dolphin Image) with the post surgical results. Were selected the pre and post surgical lateral telerradiograph (six months after orthognatic surgery) of the 25 long face patients treated with combined orthognatic surgery. Were made the prediction tracings for each method and comparing cephalometrically with the post surgical results. This protocol was repeated once more for the error method evaluation, and the statistical was made by variance analysis and Tuckey overtest. The results show more frequency of the cephalometric values' aproximation of the post surgical results when the manual method (50% of the similarity with the post surgical result), followed of the DFPlus (31,2%) and Dolphin (18,8%) softwares. The experimental condition permits to conclude that the manual method had more precision, although the previsibility of the digital methods was reasonable satisfactory.

O objetivo desta pesquisa foi comparar, por meio de análises cefalométricas, os traçados preditivos (pelo método manual e pelos programas Dentofacial Planner Plus e Dolphin Image) com os resultados pós-cirúrgicos, avaliando assim a previsibilidade dos traçados preditivos. Foram selecionadas as telerradiografias pré e pós-cirúrgicas (seis meses após a cirurgia ortognática) de 25 pacientes tratados com cirurgia ortognática combinada. Foram realizados os traçados preditivos para cada método e estes foram comparados com os resultados pós-cirúrgicos. Este protocolo foi repetido para a avaliação do erro do método, e a estatística instituída utilizou-se da análise de variância. Os resultados mostraram maior frequência de aproximações para os valores cefalométricos dos resultados pós-cirúrgicos quando o método manual foi empregado (50% de similaridade), seguido dos programas DFPlus (31,2%) e Dolphin (18,8%). A condição experimental permitiu concluir que o método de previsão manual teve maior precisão, embora a previsibilidade dos métodos digitais tenha sido razoavelmente satisfatória.
Cephalometric comparative evaluation of predictibility for surgical orthodonthic treatment in long face patients
Keywords: Orthodontics; Previsibility; Cephalometry; Orthognatic Surgery; Face; Ortodontia; Previsibilidade; Cefalometria; Cirurgia ortognática; Face